2021
DOI: 10.7717/peerj.12406
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the urinary proteome in rats with regular swimming exercise

Abstract: Purpose Urine can sensitively reflect early pathophysiological changes in the body. The purpose of this study was to explore the changes of urine proteome in rats with regular swimming exercise. Methods In this study, experimental rats were subjected to daily moderate-intensity swimming exercise for 7 weeks. Urine samples were collected at weeks 2, 5, and 7 and were analyzed by using liquid chromatography coupled with tandem mass spectromet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The level of urinary alkaline phosphatases is also reported to change in young men before and after 3 km running [ 101 ]. Similarly, swimming exercises can alter urine proteomics [ 102 ]. A study has been conducted to investigate the effects of long-distance cycling on specific urinary biomolecules [ 103 ].…”
Section: Effects Of Physical Activitiesmentioning
confidence: 99%
“…The level of urinary alkaline phosphatases is also reported to change in young men before and after 3 km running [ 101 ]. Similarly, swimming exercises can alter urine proteomics [ 102 ]. A study has been conducted to investigate the effects of long-distance cycling on specific urinary biomolecules [ 103 ].…”
Section: Effects Of Physical Activitiesmentioning
confidence: 99%
“…Pharmacologically, urinary biomarkers may indicate the utility of drugs in the body, such as predicting the efficacy of rituximab therapy in adult patients with systemic lupus erythematosus (SLE) and determining that sacubitril-valsartan is more effective than valsartan in the treatment of chronic heart failure ( Davies et al, 2021 ). In terms of exercise physiology, urine biomarkers can reflect changes in urine proteomics after exercise, thus providing a scientific basis for the rational training of athletes ( Meng et al, 2021 ). In recent years, many studies have shown that urine proteomics can also reveal biomarkers in neurodegenerative diseases and psychiatric diseases, such as Parkinson’s disease ( Virreira Winter et al, 2021 ; Seol, Kim & Son, 2020 ), Alzheimer’s disease ( Watanabe et al, 2020 ), depression ( Huan et al, 2021 ), autism ( Meng, Huan & Gao, 2021 ) and other diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacologically, urinary biomarkers can observe the utility of drugs on the body, such as predicting the efficacy of rituximab therapy in adult patients with systemic lupus erythematosus (SLE), and sacubitril-valsartan is more effective than valsartan in the treatment of chronic heart failure [21] . In terms of exercise physiology, urine biomarkers can reflect changes in urine proteomics after exercise, thus providing a scientific basis for the rational training of athletes [22] . In recent years, many studies have shown that urine proteomics can also reveal biomarkers in psychiatric diseases, such as parkinsonism [23][24] , Alzheimer’s disease [25] , depression [26] , autism [27] and other diseases.…”
Section: Introductionmentioning
confidence: 99%